Synergistic influence on microbial communities ascribed to copper and tetracycline during aerobic composting: Insights into bacterial and fungal structures - Cui, Hu; Wang, Lixia; Zhang, Jian (Frontiers in Ecology and Evolution, 2022)
There are considerable discussions aimed at ascertaining microbial communities and functions during the composting process. However, microbial succession under copper (Cu) and tetracycline (TCH)-stressed conditions has received less attention. Thus, this work analyzed the bacterial and fungal structures with high-throughput sequencing in Cu/TCH-amended composting (Cu: 0, 100 and 500 mg/kg; TCH: 0, 50 and 300 mg/kg), and the dominating controls on microbial diversity were identified using redundancy analysis (RDA) and structure equation models (SEMs). Low-concentration Cu increased the peak temperature (57℃) at the thermophilic phase. Composting phase-derived changes in bacterial and fungal communities were significant, while Cu and TCH showed a remarkable influence on fungi, but not to bacteria. Cu and TCH inhibited Firmicutes activity, while promoted Actinobacteriota growth. Low-concentration Cu and TCH had a negative effect on Basidiomycota at the thermophilic phase, and a positive influence on Chytridiomycota at the mature phase. TOC and TN were primary controls on the changes in microbial communities. NH4+-N and NO3--N were more beneficial to fungi with the contribution proportion of 42.13% and 16.85%, respectively. These findings could provide theoretical guidance for the directional research on the microbial inoculants.